Exploring Partial Overlaps Between Knowledge Systems in a Brazilian Fishing Community - Renck, Vitor; Ludwig, David; Bollettin, Paride [UNESP]; El-Hani, Charbel N. (Springer Nature, 2022)
Based on a mixed-methods study involving triad tasks and ethnobiological models, we analyze local categories and knowledge of key ethnospecies of fish exploring partial overlaps between artisanal fishers’ and academic knowledge in a fishing community in northeast Brazil. We argue that fishers’ and academic knowledge overlaps may provide common ground for transdisciplinary collaboration, while their partiality requires reflection on epistemological and ontological differences. Here, we show how knowledge of artisanal fishers can complement academic knowledge and bring about tensions that need to be addressed through intercultural dialogue. By integrating a general philosophical framework of partial overlaps with a mixed-methods study on fishers’ knowledge, we show how ethnobiology can contribute to reflective and empirically-grounded transdisciplinary practices.
Keywords: Artisanal fishers; Bahia; Itapicuru estuary; Knowledge integration; Northeast Brazil; Partial overlaps; Philosophy of ethnobiology; Transdisciplinarity